Bow-Wow's nightmare neighbors - Newgarden, Mark (Roaring Brook Press, 2014)
When mischievous ghost cats steal his sleeping cushion, Bow-Wow bravely enters a spooky house to retrieve it
Keywords: Dogs; Cats; Ghosts; Haunted houses; Neighbors; Stories without words; Bilderbuch